A pilot randomised controlled trial comparing a health-related lifestyle self-management intervention with standard cardiac rehabilitation following an acute cardiac event: Implications for a larger clinical trial - Fernandez, R.; Davidson, Patricia; Griffiths, R.; Juergens, c.; Stafford, B.; Salamonson, Y. (Elsevier Inc, 2009)
Summary. Purpose: This pilot study was to assess the feasibility of the health-related lifestyle self-management (HeLM) intervention as a strategy to decrease cardiovascular risk following acute coronary syndrome. Methods: Participants in this randomised controlled trial were recruited from a tertiary teaching hospital in metropolitan Sydney Australia. The multifaceted HeLM intervention, using the principles of the transtheoretical model, involved the use of bibliotherapy, a structured evidence-based approach to cardiovascular risk reduction, a communication strategy with general practitioners, three supportive telephone calls to participants and provision of behavioural prompts and a health record diary. Differences in behavioural and clinical outcomes between the HeLM intervention group (n=29) and the standard cardiac rehabilitation group (n=22) were assessed.Results: A total of 125 participants screened were eligible for participation in the study. Fifty-one participants, mean age 57 years (+8.78) were randomised. At the 8-week follow up, participants in the HeLM intervention group had a reduced systolic blood pressure compared to the standard care group (120.3 S.D.: 16.3 vs. 126.4 S.D.: 14.6). There were no significant differences in diastolic blood pressure and cholesterol levels between the two groups. Participants in both the intervention and control group had a reduction in waist circumference although when compared to baseline values, women in the HeLM intervention group had a greater reduction compared to those receiving standard care. Patients reported high levels of satisfaction with this intervention. Conclusions: Findings support the feasibility of implementing the health-related lifestyle self-management intervention for risk factor modification in patients with acute coronary syndrome. An adequately powered randomised controlled trial is required to test the impact of the intervention on cardiovascular risk reduction.